Come on, have a drink: The prevalence and cultural logic of social pressure to drink more. (3rd July 2016) - Mäkelä, Pia; Maunu, Antti
Abstract: Aims : We review literature and use existing quantitative and qualitative data to examine direct and indirect pressures to drink more, particularly among heavy drinking adults. Methods : Quantitative analysis uses a Finnish general population survey ( n = 2725), which included questions on direct pressure to drink and on wishes for better non-alcoholic alternatives. Experiences and cultural logics of social pressure are studied using thematic interviews of young adult Finns ( n = 52) on factors encouraging their drinking. Findings : Nearly one-half of the population reported having been pressured to drink during the past year. Pressures to drink more were reported the most among heavy and problem drinkers, and among respondents in their 20s. The qualitative data showed that indirect pressures to drink played a more significant role for the respondents. Ambivalence was created by two forces: collective drinking stands for sociability in the Finnish drinking culture so that there is a strong social norm and expectation to drink in social situations; simultaneously, drinking is considered a highly individual and autonomous activity. Conclusions : In alcohol abuse prevention, more attention should be paid to the norms that guide social and cultural possibilities of situational abstinence and the possibility to reduce drinking within drinking situations among those who drink.